The Effect of Additional Baffle Plates on Double-Stage Gravitational Water Vortex Turbine - Prasetyo, Ari; Rovianto, Eki; Adika, Dimas; Maulana, Reza; Septiyanto, Muhamad D.; Budiana, Eko P.; Hadi, Syamsul; Prabowoputra, Dandun M. (Civil Engineering Journal, 2025)
A Gravitational Vortex Water Turbine (GWVT) is an appropriate device to harness the kinetic energy of water to convert it into rotational mechanical energy in low-head. The water flow is directed into a circular basin, which can produce a vortex and can rotate the turbine blades. Turbine performance is influenced by the shape of the blade, so an optimal blade shape is required. Turbine performance is influenced by the shape of the blades, which can rotate optimally. This study aims to determine the effect of adding baffle plates in the blade on the performance of two-stage GWVT using experimental methods. The variation used is the proportion of baffle plate on the runner in the first stage with variations without baffle plate, 25%, 50%, 75%, and 100%. The data taken in the test is the torque and rotation at each additional blade plate. Torque measurement uses a rope brake system, and rotation measurement uses a tachometer. The results of the study showed that the addition of a 50% baffle plate in the first stage can capture the energy of the water vortex more optimally. A baffle plate can increase efficiency by up to 23.15% compared to the blade without the addition of a baffle plate. Doi: 10.28991/CEJ-2025-011-02-011 Full Text: PDF